Significados e usos de materiais educativos sobre hanseníase segundo profissionais de saúde pública do Município do Rio de Janeiro, Brasil Meanings and use of educational materials on Hansen disease according to public health officials in the Municipality of Rio de Janeiro, Brazil - Adriana Kelly-Santos; Simone Monteiro; Brani Rozemberg (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
O artigo objetiva refletir sobre os processos comunicativos de Programas de Controle de Hanseníase (PCH) do Sistema Único de Saúde (SUS), por meio da análise da recepção de materiais educativos por profissionais de dois serviços de saúde pública no Rio de Janeiro, Brasil. O trabalho discute em que medida a análise de impressos favorece a negociação dos sentidos e das práticas sobre hanseníase vigentes nos PCH. Foram analisados 38 materiais produzidos entre 1993 a 2005, por instituições governamentais e não-governamentais e realizados dois grupos focais com profissionais atuantes no PCH. Durante os grupos focais 6 materiais foram examinados. Os resultados revelaram a verticalidade e fragmentação nos processos comunicativos, expressas pela: ênfase em campanhas, produção centralizada, homogeneização dos públicos e conteúdos e privilégio dado ao saber biomédico. As atividades horizontais e participativas não eram comuns. Foi identificada uma lacuna entre a institucionalização do discurso da hanseníase, como alternativa à terminologia da lepra, e a sua circulação e consumo entre os diferentes atores sociais. This article reflects on the communications processes in the Hansen Disease Control Programs under the Unified National Health System (SUS) in Brazil, analyzing how professionals at two public health services in Rio de Janeiro perceive the educational materials on the disease. The article discusses how analysis of printed materials favors negotiation of prevailing meanings and practices on Hansen disease in the programs. Thirty-eight different educational materials were analyzed (produced from 1993 to 2005 by governmental and nongovernmental institutions) through two focus groups with program staff. Six materials were examined during the focus groups. The findings showed the communications processes are vertical and fragmented, with an emphasis on campaigns, centralized production of materials, homogenization of target publics, and a focus on biomedical knowledge. Horizontal and participatory activities were uncommon. A gap was identified between the institutionalization of the discourse on Hansen disease as an alternative to leprosy terminology and its circulation and uptake among different social actors.